Intramuscular vaccination against SARS-CoV-2 transiently induces neutralizing IgG rather than IgA in the saliva - Winklmeier, Stephan; Rübsamen, Heike; Özdemir, Ceren; Wratil, Paul R.; Lupoli, Gaia; Stern, Marcel; Schneider, Celine; Eisenhut, Katharina; Ho, Samantha; Wong, Hoi Kiu; Taskin, Damla; Petry, Marvin; et al. (Frontiers in Immunology, 2024)
The mucosal immunity is crucial for restricting SARS-CoV-2 at its entry site. Intramuscularly applied vaccines against SARS-CoV-2 stimulate high levels of neutralizing Abs in serum, but the impact of these intramuscular vaccinations on features of mucosal immunity is less clear. Here, we analyzed kinetic and functional properties of anti-SARS-CoV-2 Abs in the saliva after vaccination with BNT162b2. We analyzed a total of 24 healthy donors longitudinally for up to 16 months. We found that specific IgG appeared in the saliva after the second vaccination, declined thereafter and reappeared after the third vaccination. Adjusting serum and saliva for the same IgG concentration revealed a strong correlation between the reactivity in these two compartments. Reactivity to VoCs correlated strongly as seen by ELISAs against RBD variants and by live-virus neutralizing assays against replication-competent viruses. For further functional analysis, we purified IgG and IgA from serum and saliva. In vaccinated donors we found neutralizing activity towards authentic virus in the IgG, but not in the IgA fraction of the saliva. In contrast, IgA with neutralizing activity appeared in the saliva only after breakthrough infection. In serum, we found neutralizing activity in both the IgA and IgG fractions. Together, we show that intramuscular mRNA vaccination transiently induces a mucosal immunity that is mediated by IgG and thus differs from the mucosal immunity after infection. Waning of specific mucosal IgG might be linked to susceptibility for breakthrough infection.